The unity of Luke-Acts - Verheyden, Joseph (Hervormde teologiese studies, 1999)
The article contains a summary of contributions delivered at he 47th Colloquium Biblicum Lovaniense (1998) held at the Catholic University, Leuven on the subject: "The unity of Luke-Acts". The opening address was delivered by J Verheyden (Leuven) on "The Unity of Luke and Acts: What are we up to?". The contributors were: J Kremer (Vienna) - "Die dreifache Wiedergabe des Damaskuserlebnis Pauli in der Apostelgeschichte: Eine Hilfe für das rechte Verständnis der lukanischen Osterevangelien"; D Marguerat (Lausanne) -"Jusqu' où faut-il parler d'une "unité". Luc-Actes? Continuity et ruptures dans I'ævre de Luc"; JDelobel (Leuven) - "The text of Luke-Acts: A confrontation of recent theories"; R L Brawley (Chicago) - "Abrahamic covenant traditions and the characterization of God in Luke-Acts"; F W Horn (Mainz) - "Die Haltung des Lukas zum römischen Staat im Evangelium und in der Apostelgeschichte"; J A Fitzmyer (Washington) - "The role of theSpirit in Luke-Acts"; M Rese (Munster) - "The Jews in Luke-Acts: Some secondthoughts"; J Taylor (Jerusalem) - "La fraction du pain en Luc-Actes"; W Radl (Augs-burg) - "Die Beziehungen der Vorgeschichte zur Apostelgeschichte, dargestellt an Lk 2:22-39; F Neirynck (Leuven) - "Luke 4:16-30 and the unity of Luke-Acts"; C M Tuckett (Oxford) - "The Christology of Luke-Acts"; O Mainville (Montreal) - "Le messianisme de Jésus: Le rapport announce/accomplissement entre Lc 1,35 et Ac 2,33"; A Lindemann (Bethel-Bielefeld) - "Form und Funktion von Reden und Wundererzählungen im Lukas-evangelium und in der Apostelgeschichte", A Denaux - The theme of divine visits and human (in)hospitability in Luke-Acts and its Old Testament and Graeco-Roman antecedents.